Hyperbaric Oxygen Therapy in Systemic Inflammatory Response Syndrome - Débora Gouveia; Mariana Chichorro; Ana Cardoso; Carla Carvalho; Cátia Silva; Tiago Coelho; Isabel Dias; António Ferreira; Ângela Martins (Veterinary Sciences, 2022)
(1) Background: Systemic inflammatory response syndrome (SIRS) can occur due to a large number of traumatic or non-traumatic diseases. Hyperbaric oxygen therapy (HBOT) may be used as a main or adjuvant treatment for inflammation, leading to the main aim of this study, which was to verify the applicability of HBOT as a safe and tolerable tool in SIRS-positive dogs. (2) Methods: This prospective cohort study included 49 dogs who showed two or more parameters of SIRS, divided into the Traumatic Study Group (n = 32) and the Non-Traumatic Study Group (n = 17). All dogs were submitted to HBOT for 60–90 min sessions, with 2.4–2.8 ATA. (3) Results: This study revealed that 73.5% (36/49) of dogs showed improvement, and the minimum number of HBOT sessions was two, with a mean of 12.73. The number of days between diagnosis and the beginning of HBOT showed statistical significance (p = 0.031) relative to the clinical outcome. No dogs showed any major side effects. (4) Conclusions: We concluded that HBOT may be safe and tolerable for SIRS-positive dogs, and that it should be applied as early as possible.